Empowering Rural Communities through Financial Literacy and Entrepreneurship Training - Afriani, Gusma (Assoeltan: Indonesian Journal of Community Research and Engagement, 2025)
Rural communities often face barriers in accessing financial knowledge and entrepreneurial opportunities, limiting their economic independence and development potential. This community service aimed to empower rural micro-entrepreneurs through integrated financial literacy and entrepreneurship training using the Participatory Rural Appraisal (PRA) approach. Conducted in Desa Mekar Sari, West Bandung Regency, the program involved 30 participants in participatory workshops, mentoring, and digital entrepreneurship sessions. Data were collected through observation, interviews, and pre–post tests, and analyzed using mixed methods with Pearson correlation tests and thematic analysis. Results showed a 42% improvement in financial literacy and a strong correlation (r = 0.76) between financial knowledge and entrepreneurial competence. Participants demonstrated better budgeting, record-keeping, and digital marketing skills, alongside stronger collaboration through a community-based entrepreneurship forum. The study concludes that PRA-based empowerment effectively bridges knowledge and practice, fostering sustainable local entrepreneurship. This program contributes to the discourse on participatory, inclusive, and digital-based rural economic empowerment.